CHH demethylation in the ZmGST2 promoter enhances maize drought tolerance by regulating ROS scavenging and root growth - Xiaocui Yan; Mengjie Zhang; Yuan Zhong; Tinashe Zenda; Songtao Liu; Anyi Dong; Mengyu Kou; Jialong Liu; Nan Wang; Huijun Duan (BMC Plant Biology)
Abstract As an important food crop worldwide, maize is frequently impacted by drought stress. It is of great significance to study its drought resistance genes and mechanisms, in which DNA methylation modification in the promoter region plays a key role in regulating gene expression and stress resistance. In this study, using PEG6000 and 5-azadC to treat different drought-tolerant maize inbred lines (drought-tolerant R99 and drought-sensitive Mo17), combined with transcriptomic analysis, identified the gene ZmGST2 as being related to drought resistance. Subsequently, the methylation changes in its promoter region were further analyzed. The results indicated that the expression level of ZmGST2 was closely related to the methylation status of its promoter region under drought stress. Specifically, in drought-resistant R99, a decrease in methylation (demethylation) occurred within the CpG island of the ZmGST2 promoter region after drought treatment, which facilitated the expression of this gene and thereby enhanced drought resistance in maize. However, in the drought-sensitive Mo17, this demethylation change did not occur, resulting in reduced drought resistance. Further phenotypic analysis revealed that overexpression of ZmGST2 could enhance the reactive oxygen species scavenging ability in maize roots, improve root growth, and significantly enhance drought resistance. Overall, this study provides both a new candidate gene and a novel approach for molecular breeding aimed at enhancing maize drought resistance.